Sex disparities in acute myocardial infarction care and outcomes. Issue 5 (10th May 2018) - Gul, Burcu; Kozuma, Ken; Haimi, Ido; Zhao, Weiying; Simonton, Charles; Ying, Shih‐Wa; Buda, Alexandra; Mehta, Sameer; Baumbach, Andreas; Lansky, Alexandra
Abstract: Aim: We investigated sex‐based and regional outcomes after contemporary percutaneous coronary intervention (PCI) with the Xience V stent in patients with acute myocardial infarction (AMI). Methods and Results: This patient level pooled analysis includes three multi‐center, prospective post‐market registries performed in the US, Japan, and China. A total of 1, 938 patients treated with Xience V stents in the setting of AMI were enrolled. Compared to men, women had higher major adverse cardiac events (MACE) (14.1% vs. 9.8% P  < 0.01, RR 1.4, 95% CI 1.1–1.4) and all‐cause mortality (10% vs. 6.2% P  < 0.01, RR 1.61, 95% CI 1.14–2.27) at one year, without any significant difference in device specific outcomes of target vessel failure (TVF). US patients compared to the patients from China and Japan had increased MACE (female: 18% vs. 7.1%, P  = 0.0012, male: 15.7% vs. 4.1%, P  < 0.0001). Multivariable analysis demonstrated that major bleeding was the strongest predictor of MACE (OR 10.51, 95%CI 4.01–27.50, P  < 0.0001), MI (OR 4.26, 95%CI 1.37–13.29, P  = 0.012), and all‐cause death (OR 5.3, 95%CI 2.32–12.13, P  < 0.0001). Conclusion: Women with AMI who underwent PCI with XIENCE DES have higher all‐cause mortality at one year in compared to men. Region based outcomes demonstrated increased MACE among US patients compared to the patients from China and Japan. After adjusting for differences in demographics, major bleeding, rather than female sex, predicted the higher observed all‐cause mortality.